Insight into the sequence-structure relationship of TLR cytoplasm's Toll/Interleukin-1 receptor domain towards understanding the conserved functionality of TLR 2 heterodimer in mammals. Issue 15 (2nd September 2021) - Ghosh, Soumya Kanti; Saha, Bhaskar; Banerjee, Raja
Abstract: The signaling response of TLR2 to ligands has always been as a homodimer or in heterodimerization with TLR1/TLR6. The Toll/Interleukin-1 Receptor (TIR) domain of the TLR cytoplasmic region regulates the dimerization and interactions with adaptor molecules to build an active signaling complex. To understand the conservation of functionality of the TLR2-heterodimers between the distantly related species human(h) and mice(m), the pattern of TIR-TIR interaction in heterodimers has been studied through the sequence-structural point of view. Comparative analysis of primary sequence and structural pattern of TLRs(1/2/6) corroborates higher sequence homology between TLR1 and TLR6. Molecular docking analysis of TLR2-TLR1 and TLR2-TLR6 cytoplasmic dimers in both mouse and human have identified that for interaction the BB loop/near-BB loop residues of TLR2 are involved with the near-DD loop of TLR1 and DD loop residues of TLR6 within the TIR domains, which may cause to differential signaling. Molecular dynamics simulation of dimers for both human and mice species recognize stable interface between near-BB/BB loop region of TLR2 and discrete near-DD and DD loop region of TLR1 and TLR6 respectively. The observed dimerization pattern in both the species is further supported by Alanine scanning mutation study. However, Solvent Accessible Surface Area (SASA) of BB and DD loop regions of the cytoplasmic monomers and the heterodimers suggests that while TLR2 BB loop is actively associated as the dimer interface with its heterodimer partners in both the species, the DD loop acts as the active interfacing region in hTLR1 and mTLR6. Communicated by Ramaswamy H. Sarma